VD_FINDINFO Jug / 2024 / 30 vom 28. März 2023 - VD Tribunal cantonal (2023)
RÉCUSATION, DÉFENSE D'OFFICE, CONSTATATION DES FAITS, ERREUR SUR LES FAITSDROIT PÉNAL, DÉNONCIATION CALOMNIEUSE | 13 CP, 303 ch. 1 al. 1 CP, 132 al. 1 let. b CPP (CH), 398 al. 3 let. b CPP (CH), 56 let. f CPP (CH), 58 CPP (CH)